CASL: A Guided Tour of its Design - Mosses, Peter D. (BRICS Report Series, 1998)
Casl is an expressive language for the specification of functional requirements and modular design of software. It has been designed by CoFI, the international Common Framework Initiative for algebraic specification and development. It is based on a critical selection of features that have already been explored in various contexts, including subsorts, partial functions, first-order logic, and structured and architectural specifications. Casl should facilitate interoperability of many existing algebraic prototyping and verification tools. This guided tour of the Casl design is based closely on a 1/2-day tutorial held at ETAPS’98 (corresponding slides are available from the CoFI archives). The major issues that had to be resolved in the design process are indicated, and all the main concepts and constructs of Casl are briefly explained and illustrated - the reader is referred to the Casl Language Summary for further details. Some familiarity with the fundamental concepts of algebraic specification would be advantageous.